Optimizing Administrative Professionalism: A Strategic Approach to Elevate Clientele Satisfaction in Service-Oriented Environments - Mary Rose Montano; Aveto M. Dasal; Jr., Renante A. Artificio; Anna Rhea C. Opeña; Meljhon G. Mosca (People and Behavior Analysis, 2024)
Professionalism is crucial in shaping client experience in organizations, yet many organizations lack strategies to enhance staff conduct, leading to inconsistent service, communication gaps, and inadequate training.  Essential qualities such as competence, courtesy, honesty, integrity, and specialized knowledge significantly impact client interactions, complaint resolution, and organizational image. This study, conducted at the City College of Calamba, Philippines, surveyed 1,126 students to assess their perceptions of professionalism among administrative personnel providing student services and evaluate customer satisfaction.   Using a descriptive correlational approach with stratified random sampling and simple statistical treatment such as mean and Goodman and Kruskal's Gamma Correlation, the study established a correlation between staff professionalism and satisfaction, proposing a development program based on its findings. The survey found high levels of professionalism and customer satisfaction, recognized staff strengths in professional communication and accountability, and indicated areas for growth in problem-solving. The significant relationships between job performance, service delivery, ethics, and satisfaction highlight professionalism’s impact on consumer perspectives. The novelty of this study lies in its focus on the correlation between professionalism and satisfaction within an educational setting, offering insights for targeted development programs. Limitations include a small sample size, which may affect generalizability, reliance on self-reported data, cross-sectional design, and a focus on one institution, which may overlook broader contextual nuances.